Is the interrogating/interviewing of crime perpetrators no longer suspect? A personal commentary on 25 years of progress - Bull, Ray (International journal of police science & management, 2024)
This article focuses on some of the main developments regarding the interviewing of suspects during the past 25 years. It contains a personal commentary on: the 25 years ago publication of the 1999 Milne and Bull book; the evolution of the KREATIV approach in Norway; when to disclose information to suspects; a major decision by Wicklander-Zulawski & Associates; the High-Value Detainee Interrogation Group; the Council of Europe's document; the views of jail inmates; the Méndez Principles; the use of cognitive empathy; the American Psychology-Law Society's consultation document.